Influence of cimetidine and experimental diabetes mellitus on gabapentin pharmacokinetics in rats - Lima Benzi, Jhohann Richard de (2017)
Univ Sao Paulo, Sch Pharmaceut Sci Ribeirao Preto, Ribeirao Preto, Brazil